First glacier inventory and recent changes in glacier area in the monte San Lorenzo region (47ºS), Southern Patagonian Andes, South America - Falaschi, Daniel; Bravo, Claudio; Masiokas, Mariano Hugo; Villalba, Ricardo; Rivera, Andrés (Arctic, Antarctic, and Alpine Research)
We present the first glacier inventory of the Monte San Lorenzo region (47º35′S, 72º18′W) in the southern Patagonian Andes of Chile and Argentina. This region contains the largest and easternmost glaciers at these latitudes in South America. The inventory was developed using a combination of ASTER and Landsat ETM + scenes from 2005 and 2008, respectively, and a semi-automatic band ratio approach to map glacier ice. Manual corrections were applied to include debris-covered ice and ice in cast shadows. We inventoried 213 glaciers that cover a 2005/2008 total area of ca. 207 km2 and lie between 520 m and 3700 m in elevation. Landsat TM images acquired in 1985 and 2000 were subsequently used to assess changes in glacierized area over the 1985–2008 interval. Based on all available information, we determined an 18.6% reduction in the total glacier area since 1985. Glaciers smaller than 1 km2 have shown highly variable (0–100%) relative areal reduction, whereas the formation and growth of proglacial lakes promoted rapid recession of the, larger valley glaciers, which concentrate the major ice losses, representing ca. 32% of the total glacier area reduction. Glacier fragmentation has occurred for 50% of the ice bodies larger than 1 km2. These results agree with the generalized pattern of glacier retreat observed throughout the Patagonian Andes, but the lack of detailed meteorological and glaciological data in the area preclude a more refined analysis of the climate-glacier relationships and processes explaining the recent glacier trends. Fil: Falaschi, Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas. Científico Tecnológico Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: Bravo, Claudio. Departamento de Geofísica. Universidad de Chile; Chile Fil: Masiokas, Mariano Hugo. Consejo Nacional de Investigaciones Científicas y Técnicas. Científico Tecnológico Mendoza. Instituto Argentino de Nivología, Glaciología y Ciencias Ambientales; Argentina Fil: ...